2012
DOI: 10.1155/2012/845673
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition and Characterization of Nanocrystalline Ni‐Mo Catalysts for Hydrogen Production

Abstract: Ni-Mo nanocrystalline deposits (7–43 nm) with a nodular morphology were prepared by electrodeposition using direct current from citrate-ammonia solutions. They exhibited a single Ni-Mo solid solution phase. The size of the nodules increased as electroplating current density increased. The molybdenum content—estimated using EDX analysis—in the deposits decreased from about 31 to 11 wt% as the current density increased from 5 to 80 mA·cm−2. The highest microhardness value (285 Hv) corresponded to nanodeposits wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 34 publications
3
31
0
4
Order By: Relevance
“…6). These results are in close agreement with data reported in numerous papers [7][8]26]. Moreover, an increase in the rate of mass transport causes reduction of the current efficiency related to the higher content of (diffusion controlled) molybdenum in alloys [19].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…6). These results are in close agreement with data reported in numerous papers [7][8]26]. Moreover, an increase in the rate of mass transport causes reduction of the current efficiency related to the higher content of (diffusion controlled) molybdenum in alloys [19].…”
Section: Resultssupporting
confidence: 92%
“…These effects have resulted in a decrease of the relative content of molybdenum in the alloy with an increase of current density (or cathode potential decrease). Also, during co-deposition process a significant increase of the hydrogen evolution is observed due to the low hydrogen overvoltage on the molybdenum oxides or on molybdenum alloys [25][26]. Furthermore, on the basis of SEM, XRD and XPS analysis of resulting deposits, it was found that metallic, nanocrystalline and homogenous coatings are obtained when the potential is shifted to more negative values than -1.35V/SCE.…”
Section: Resultsmentioning
confidence: 99%
“…Electrodeposited Ni-Mo composites showed higher corrosion rates (0.035-1.795 mm/y) compared to the corrosion rates of Ni-Mo electrodeposited alloys (4.7-8.3 × 10 −3 mm/y) [16]. This result would be attributed to the non homogeneity and the rough surface of the Ni-Mo composites compared to the surface of Ni-Mo alloys.…”
Section: Discussionmentioning
confidence: 83%
“…surface. The morphology of the composite films shows rougher, more irregular and more developed morphology than that of the alloy films [16].…”
Section: Methodsmentioning
confidence: 87%
“…Electrodeposition has a lot of advantages over other surface modification techniques such as low cost and capability of manufacturing multicomponent nanocrystalline materials for many energy applications [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%